Detection of Bacterial Vaginosis and Comparison Of Clinical & Microbiological Methods Among Women Attending Chittagong Medical College Hospital - Ara, Nura Nasrin Rowshan; Husain, Md Anwar; Akter, Nasima; Rahman, Md Mostafizur; Chowdhury, Abu Hena Md Saiful Karim (Journal of Chittagong Medical College Teachers' Association, 2016)
Bacterial vaginosis is a special public health concern in the world because of high burden of reproductive and pregnancy related morbidity. This present study was undertaken to detect the bacterial vaginosis in reproductive women by different clinical and microbiological methods on patients attending at the out patient department of Gynaecology and Obstetrics of Chittagong Medical College Hospital. A total of 170 sexually active female in the age group of 15-45 years, with abnormal vaginal discharge were selected for the study. In this study bacterial vaginosis was detected by Amsel clinical criteria (Clinical method) Gram stain Nugent criteria (Gold Standard) culture and by newly developed BV assay test and compared these methods. Out of 170 study cases, 43(25.30%) cases were diagnosed as bacterial vaginosis by Amsel criteria, 45(26.47%) cases were positive by Nugent criteria, 46(27.06%) cases were positive by BV assay test and 38(22.35%) cases were culture positive for Gardnerella vaginalis. Sensitivity of the clinical criteria (Amsel) BV assay test, and culture were 95.5%, 97.8% and 84.4% respectively in response to Gold standard Nugent criteria. All these findings make the BV assay test more accurate and reliable screening procedure for the diagnosis of bacterial vaginosis which help our physicians and patients. JCMCTA 2016 ; 27 (1) : 40 - 45